Susceptibility of Rhodnius pallescens (Hemiptera: Reduviidae) of fifth instar nymph to the action of Beauveria spp. (2003)
ABSTRACT: Laboratory bioassays were performed to determine the susceptibility of 5th instar nymphs of the insect Rhodnius pallescens Barber to the entomopathogenic fungi, Beauveria spp. The insects were bred and kept at the Mycology Laboratory, Instituto de Biología, Universidad de Antioquia. Two strains of the entomopathogenic fungi Beauveria bassiana were isolated from the triatomine bug R. pallescens and two of B. brongniartii from the weevil Homalinotous validus (Olivier), both of which inhabit Attalea butyracea palms in the San Onofre region of the Colombian department of Sucre. The pathogenicity of Beauveria isolates to R. pallescens was studied by exposing laboratory-reared insects to fungal inocula consisting of 1 x 107 spores/ml smeared on pieces of canvas. The different isolates produced variable degrees of mortality in the bugs, ranging from 77.5% B. bassiana (Bb UdeA14) to 100% B. brongniartii (Bt UdeA16) at 22 days. LT50 values of 10,11 and 12 days were estimated for the isolates B. bassiana (Bb UdeA14), B. brongniartii (Bt UdeA15) and B. bassiana (Bb UdeA13) respectively. The lowest recorded LT50 value was 7 days for B. brongniartii (Bt UdeA16), this isolate being significantly more effective than the others and the control (X2 = 200.84, p< 0.0001). Fifth instar nymphs of R. pallescens were more susceptible to B. brongniartii (Bt UdeA16) than the other strains tested, and 50% of the insects showed mycosis 10 days after being exposed to this strain (X2 = 47.08, p < 0.0001).